Self‐Powered and Interface‐Independent Tactile Sensors Based on Bilayer Single‐Electrode Triboelectric Nanogenerators for Robotic Electronic Skin - Lin, Yucheng; Duan, Shengshun; Zhu, Di; Li, Yinghui; Wang, Binghao; Wu, Jun (Advanced intelligent systems, 2023)
Self‐powered flexible tactile sensors based on triboelectric nanogenerators (TENGs) can be of use in the development of robotic intellisense and interaction. Such sensors typically use triboelectronegative material as top layer, requiring contacting and separating with specific interface material to operate, and may result in suboptimal performance under practical conditions. Herein, a self‐powered interface‐independent tactile sensor array that is based on bilayer single‐electrode TENGs is reported. By integrating both triboelectronegative and triboelectropositive layers in the structure, the sensor overcomes the material restriction of top layer and could sense applied pressure from any material. Furthermore, a 5 × 5 sensor array is fabricated to realize the detection of contact point and the recognition of trajectory. Last, the sensor array is successfully implemented as electronic skin (e‐skin) in a robotic hand for tactile sensing and human–machine interaction. In this regard, it can be envisioned that such tactile sensors possess a promising application in intelligent robots including robotic e‐skin and artificial intelligence. Flexible, self‐powered, and interface‐independent tactile sensors are of great value for robotic intellisense and human–machine interaction. Herein, a generic tactile sensor based on bilayer single‐electrode TENGs independent of interface materials for robotic perception is reported. A human–machine interaction system, implementing precise contact point detection and interactive feedback, is demonstrated on robotic hand.